2021
DOI: 10.17977/jptpp.v6i4.14719
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Bahan Ajar Berbicara untuk Pelajar BIPA Tingkat Pemula Tinggi

Abstract: <p><strong>Abstract:</strong> This research aims to produced speaking teaching materials for BIPA students in novice high level. The development model used is Borg and Gall development model. The result of the development is the teaching material developed have three characteristics, namely the topics in the teaching material according to the needs of BIPA students in novice high level, the speaking material is based on language functions for verbal communication needs, and the level of Indon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…It is related to the contextual approach, considering that its application must be adapted to the context of actual language use (Melati et al, 2022;Pangesti, 2017;Suryani, 2016). The communicative approach is a learning approach that emphasizes aspects of communication, interaction, and increasing linguistic competence and language skills (Arumdyahsari et al, 2016;Pangesti & Wurianto, 2018). Previous research has even found that effective learning for students is 'communicative learning' (Wong & Nunan, 2011).…”
Section: Pedagogical Implication On Grammar Learning Strategies Of In...mentioning
confidence: 99%
“…It is related to the contextual approach, considering that its application must be adapted to the context of actual language use (Melati et al, 2022;Pangesti, 2017;Suryani, 2016). The communicative approach is a learning approach that emphasizes aspects of communication, interaction, and increasing linguistic competence and language skills (Arumdyahsari et al, 2016;Pangesti & Wurianto, 2018). Previous research has even found that effective learning for students is 'communicative learning' (Wong & Nunan, 2011).…”
Section: Pedagogical Implication On Grammar Learning Strategies Of In...mentioning
confidence: 99%
“…Berdasarkan yang dikatakan oleh (Adipta, Maryaeni, and Hasanah 2016) anak yang masih duduk di bangku sekolah dasar menyukai buku cerita dan bergambar yang penuh warna. Hal ini juga dipertegas oleh (Arumdyahsari, Hs, and Susanto 2016) bahwa dalam prancangan bahan ajar harus memiliki keseimbangan antara teks dan ilustrasi serta diwakilkan dengan warna agar dapat menimbulkan minat serta motivasi belajar peserta didik.…”
Section: Kebutuhan Bahan Ajar Modul Pendidikan Kepramukaan Berbasis K...unclassified
“…Development of BIPA teaching materials for listening skills (Nirmalasari, 2022). Development of teaching materials for beginner-level BIPA students' speaking skills (Ramadhani et al, 2016). Development of BIPA teaching materials for reading skills (Nuraeni, 2016;Puspita et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Development of BIPA teaching materials for reading skills (Nuraeni, 2016;Puspita et al, 2021). Speaking teaching materials were developed for high beginner-level BIPA students (Asyah et al, 2021;Pranandari, 2019). Development of writing teaching materials for BIPA students at the beginning (Zein et al, 2021).…”
Section: Introductionmentioning
confidence: 99%